Relationship between Family Support and Compliance of Post-Stroke Clients Undergoing Physiotherapy in the Medical Rehabilitation Room of Pariaman Hospital - Aulia Asman; An Aulingga Asman (Journal of World Future Medicine, Health and Nursing, 2023)
One of the degenerative diseases whose incidence has increased recently is stroke. The recovery rate of stroke is still low, as many as 15-30% of patients will experience paralysis. One of the healing processes is to follow the physiotherapy program. In the physiotherapy unit of Pariaman Hospital, more than half (50%) were not compliant with physiotherapy. The purpose of this study was to determine the relationship between family support and client compliance with physiotherapy in the physiotherapy unit of Pariaman Hospital.Stroke is an acute vascular injury to the brain, or a severe and sudden injury to the blood vessels of the brain. Injury can be caused by blockage of blood clots, narrowing of blood vessels, blockage or rupture of blood vessels. Physiotherapy is a health service that is carried out for the healing process. The implementation is in accordance with the degree of disability experienced by the client. This research is descriptive analytic with cross sectional approach. The population is stroke clients who follow physiotherapy in the physiotherapy unit of Pariaman Hospital, with sampling techniques using accidental sampling which amounted to 52 people. Data were collected by interview in accordance with the questionnaire provided and the data were processed by SPSS and then analyzed univariately and bivariately. The results of this study obtained 28 (53.8%) family support that played a role there were 3 (10.7%) clients who were not compliant with undergoing physiotherapy and from 24 (46.2%) family support did not play a role there were 22 (91.7%) clients who were not compliant with undergoing physiotherapy, P Value = 0.025 <0.05 means Ha accepts which means there is a significant relationship between family support and compliance with undergoing physiotherapy for post-stroke patients in the medical rehabilitation room of Pariaman Hospital. to increase client compliance, health workers can provide counseling on the importance of family support in increasing stroke client compliance to follow physiotherapy for the client's healing process.